PEDAGOGICAL AND PSYCHOLOGICAL OPPORTUNITIES FOR DEVELOPING ESSENTIAL PROFESSIONAL QUALITIES IN FUTURE PHYSICAL EDUCATION TEACHERS - Abdullayev Rustam Abduvaliyevich (International Scientific and Current Research Conferences, 2024)
This article highlights the research in the field of motivation conducted by foreign scholars, with a particular focus on G. Allport's theory of functional autonomy of motives, which holds a prominent position. In this theory, motives are interpreted as processes of transformation and systematic development. In his concept, G. Allport widely utilizes ideas related to general systems theory, especially the notion of open systems.